Making Nothing Happen Five Poets Explore Faith and Spirituality. - D'Costa, Gavin; Nesbitt, Eleanor; Pryce, Mark.; Shelton, Ruth.; Slee, Nicola (Farnham : Ashgate Publishing Ltd, 2014)
This is a conversation between five poet-theologians broadly within the Christian tradition who together form The Diviners. Each poet offers a reflection on how they understand the relation between poetry and faith, rooting their reflections in their own writing, and illustrating discussion with a selection of their own poems and opening up issues for deeper exploration and reflection. This book will interest poets, theologians and all those committed to the practice and nurturing of a contemplative attitude to life in which profound attention and respect are offered to words and to the creati.
Cover; Contents; Notes on Contributors; Foreword; Acknowledgements; Introduction; 1 (W)riting like a Woman: In Search of a Feminist Theological Poetics; 2 Steady until Sundown: Searching for the Holy; 3 Taking Form: On Becoming a Christian Poet; 4 Where Poems Come From: Spirituality, Emotion and Poiesis; 5 The Miracle of Poetry: Divine and Human Creativity; Index
Description based upon print version of record.
Keywords: Religion and poetry; Spirituality -- Christianity; English poetry -- 21st century -- History and criticism; Spirituality in literature; RELIGION / Christian Life / General; Electronic books